Coronary risk factors in various occupational groups: the Oslo study. Issue 2 (June 1977) - Holme, I; Helgeland, A; Hjermann, I; Leren, P; Lund-Larsen, P G
Abstract : Coronary risk factors (CRF) have been recorded for nearly 15 000 men aged between 40 and 49 living in Oslo in 1972. These data are matched with the 1970 census data for Norway so as to analyse CRF within various occupational groups. A fairly good agreement between mortality statistics for Norway and CRF was found in many occupations. For instance, persons in pedagogical work have low total mortality rates consistent with their low coronary risk factors. Taxi and busdrivers, on the other hand, have been reported to have mortality rates from lung cancer and coronary heart disease consistent with their high smoking prevalence, serum triglycerides, and cholesterol levels.